Transcranial direct-current stimulation modulates offline visual oscillatory activity: A magnetoencephalography study. (March 2017) - Heinrichs-Graham, Elizabeth; McDermott, Timothy J.; Mills, Mackenzie S.; Coolidge, Nathan M.; Wilson, Tony W.
Abstract: Transcranial direct-current stimulation (tDCS) is a noninvasive neuromodulatory method that involves delivering low amplitude, direct current to specific regions of the brain. While a wealth of literature shows changes in behavior and cognition following tDCS administration, the underlying neuronal mechanisms remain largely unknown. Neuroimaging studies have generally used fMRI and shown only limited consensus to date, while the few electrophysiological studies have reported mostly null or counterintuitive findings. The goal of the current investigation was to quantify tDCS-induced alterations in the oscillatory dynamics of visual processing. To this end, we performed either active or sham tDCS using an occipital–frontal electrode configuration, and then recorded magnetoencephalography (MEG) offline during a visual entrainment task. Significant oscillatory responses were imaged in the time-frequency domain using beamforming, and the effects of tDCS on absolute and relative power were assessed. The results indicated significantly increased basal alpha levels in the occipital cortex following anodal tDCS, as well as reduced occipital synchronization at the second harmonic of the stimulus-flicker frequency relative to sham stimulation. In addition, we found reduced power in brain regions near the cathode (e.g., right inferior frontal gyrus [IFG]) following active tDCS, which was absent in the sham group. Taken together, these results suggest that anodal tDCS of the occipital cortices differentially modulates spontaneous and induced activity, and may interfere with the entrainment of neuronal populations by a visual-flicker stimulus. These findings also demonstrate the importance of electrode configuration on whole-brain dynamics, and highlight the deceptively complicated nature of tDCS in the context of neurophysiology.